=> (xy-2x)+(y-2)+3 = 0
=> (y-2).(x+1)+3 = 0
=> (y-2).(x+1) = -3
Đến đó bạn dùng quan hệ ước bội mà giải nha
Tk mk nha
xy -2x + y + 1 = 0
x(y -2) + y + 1 -3 = 0-3
x(y -2) + y - 2 = -3
x(y -2) + (y - 2) = -3
(x+1)(y - 2) = -3
\(\Rightarrow\)x+1=-3 hoặc y - 2 = -3
\(\Rightarrow\)x =-3-1 hoặc y = -3+2
\(\Rightarrow\)x =-4 hoặc y = -1
Vậy. .......
Ta có xy-2x+y+1=0
<=> xy-2x+y=-1
<=> x(y-2)+(y-2)=-3
<=> (y-2)(x+1)=-3
=> x+1 và y-2 là ước của -3
Ta có bảng sau:
x+1 | -3 | -1 | 1 | 3 |
x | -4 | -2 | 0 | 2 |
y-2 | 1 | 3 | -3 | -1 |
y | 3 | 5 | -2 | 1 |
Vậy...
\(xy-2x+y+1=0.\)
\(\Leftrightarrow\left(x+1\right)\left(y-2\right)=-3=-1.3=1.-3=3.-1=-3.1\)
x+1 | -3 | -1 | 1 | 3 |
y-2 | 1 | 3 | -3 | -1 |
x | -4 | -2 | 0 | 2 |
y | 3 | 5 | -1 | 1 |
Vậy có 4 cặp....